2023
DOI: 10.3390/v15040938
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response and Activation of Coagulation after COVID-19 Infection

Abstract: SARS-CoV-2 (COVID-19) infection is responsible for causing a disease with a wide spectrum of clinical presentations. Predisposition to thromboembolic disease due to excessive inflammation is also attributed to the disease. The objective of this study was to characterize the clinical and laboratory aspects of hospitalized patients, in addition to studying the pattern of serum cytokines, and associate them with the occurrence of thromboembolic events. Methodology: A retrospective cohort study with 97 COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In patients with acute-on-chronic liver failure, there is a correlation between prothrombin activity, infection, and poor prognosis ( 41 43 ). While prothrombin activity is primarily used to assess clotting function, there is extensive interaction between the clotting system and the immune system ( 44 ). A study on HBV-ACLF revealed a correlation between white blood cell count, lymphocytes, and peripheral T lymphocytes with prothrombin activity (PTA) ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with acute-on-chronic liver failure, there is a correlation between prothrombin activity, infection, and poor prognosis ( 41 43 ). While prothrombin activity is primarily used to assess clotting function, there is extensive interaction between the clotting system and the immune system ( 44 ). A study on HBV-ACLF revealed a correlation between white blood cell count, lymphocytes, and peripheral T lymphocytes with prothrombin activity (PTA) ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Critical to the pathophysiology of COVID-19 is the pro-inflammatory milieu orchestrated by elevated levels of cytokines, including interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α), among others [ 3 ]. This cytokine storm contributes to systemic inflammation, vascular endothelial dysfunction, and tissue damage, culminating in acute respiratory distress syndrome (ARDS) and multiorgan dysfunction [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged state of inflammation present since the first phases of SARS-CoV-2 infection [ 5 ] induces dysfunctions after viral clearance, and it is responsible of several coagulation-based abnormalities in patients with long COVID [ 5 ], especially in the presence of thrombophilia [ 6 ].…”
mentioning
confidence: 99%